IPTEKS AUDIT INTERNAL PADA PT. BANK SULUTGO MANADO - Rondonuwu, Feilen Grace; Rundengan, Fanda D.P. (Universitas Sam Ratulangi, 2018)
Internal auditing or internal inspection is a part contained in a company that plays a role in an organization or company that functions to test and see how activities in an organization or company are carried out or carried out.According to Sukrisno Agoes in his book Auditing (examination of accountants) it was stated that: